SCHOOL AND COMMUNITY: REFLECTING PARTNERSHIPS FOR VALUES EDUCATION - Marques da Silva, Claudiele Carla; De Stefano Menin, Maria Suzana [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
In this paper we will discuss the possible relationship between Values Education projects developed in public schools and the effect on their surrounding communities. We investigated these relationships through the use of specific literature and analyzed 169 experiments of Moral Education collected through questionnaires in public secondary schools (6th to 9th grade) and high school in the state of Sao Paulo. To analyze these answers, we used software Alceste, and, in addition, the content analysis. The relationship between school and community is highlighted in the literature as complex, nonlinear and marked by tensions and contradictions. The results from of the experiments conducted by the schools, found that more than half of the projects was related to the external community. The projects analyzed were related to the external community because of the problems, needs or values experienced by students and their families or for the account of the specificities and needs of the neighborhood, as well as the need to involve parents and projects.
Keywords: Moral Education; Community; Public school